IMPROVING THE AL-QUR'AN TAHFIDZ PROGRAM THROUGH THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT - Rokhmah, Dewi; Almukarromah, Khaerunnisa; Putriyani, Putriyani; Wakhyudin, Muhammad Fahd (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to determine the improvement of the Al-Qur'an memorization program through the implementation of Total Quality Management at the Modern Islamic Boarding School Muhammadiyah Boarding School Bumiayu. This study uses a qualitative research type. Data collection methods in this study are observation, documentation, and interviews. Data were obtained directly from the subjects who provided information to the researcher, namely Mudir, Wakil Mudir, Waka Tahfidz, Tahfidz Teachers, and Santri. The data analysis method used through the stages of data collection, data reduction, data presentation, and drawing conclusions. From the results of the study, it was concluded that the improvement of the Al-Qur'an memorization program through the implementation of Total Quality Management at the Modern Islamic Boarding School Muhammadiyah Boarding School Bumiayu includes: determining memorization targets, tahsin Al-Qur'an, halaqah tahfidz, determining the method of memorizing Al-Qur'an, determining the time to memorize, time and activities to memorize, Tasmi' (memorization deposits), and tahfidz exams. Meanwhile, the implementation of TQM in the Al-Qur'an memorization program at the Modern Islamic Boarding School Muhammadiyah Boarding School Bumiayu is based on four TQM principles, namely customer focus, obsession with quality, teamwork, and continuous system improvement.